Pengaruh Warna Polibag, Aplikasi Mikoriza dan Pupuk P terhadap Perakaran Bibit Kelapa Sawit (Elaeis guineensis Jacq.) - Mardiana Wahyuni; Muhammad Maulana Ghifari; Mariani Sembiring (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
Seedling growth in the field is largely determined by the growth of plants during the nursery. The use of polybags should be black so that the roots in the nursery can develop optimally. Mycorrhiza are structures formed by symbiotic associations with root pathogen infections. Phosphate is a macro element that is very important for plant growth. The place of the research was conducted in the STIPAP Field Practice Field in Medan from February to June 2019. This study used a Factorial Randomized Block Design (RBD) with two series (Black and White Polybags) and two factors studied, namely: Mycorrhiza Factor (M) consists of 3 levels, M0 = 0 g / seed, M1 = 40 g / seed, M2 = 80 g / seed. Fertilizer Factor P (P) consists of 3 levels, P0 = 0 g / seed, P1 = 50 g / seed, P2 = 100 g / seed. The parameters measured were plant height, number of leaves, canopy and root dry weight, mycorrhiza infection and P nutrient content. The results showed that mycorrhiza treatment on black polybags had a significant effect on seedling height, and root dry weight. The white polybag has a significant influence on the dry weight of the roots. The application of P fertilizer on black polybag has a very significant effect on root dry weight. The white polybag has a significant influence on the dry weight of the roots. In the black polybag, Mycorrhiza interacts real and very real by giving P fertilizer to the height of the seedlings, and the dry weight of the roots. The white polybag has a very significant effect on the dry weight of the roots.